Performance Prediction Criteria Based on Yearling Training Cycle Data for World-Class Athletes’ Tiny 1000-Meter Kayak Teams: A Case Study - Stanislav Dadelo; Ričardas Nekriošius; Rūta Dadelienė (Life)
This research aimed to identify optimal performance needs based on physiological tests of kayakers, revealing body adaptations and critical training periods within a yearly training cycle. It sought to develop performance selection protocols for teams and provide evidence-based strategies for future training. Methods: The male athletes underwent routine physiological testing, considering medical limitations. A preparation year plan was established: six months for preparation, one month for the first competition, two months for further preparation, one month for the second competitor, and two months for transition. The athletes faced twelve tests at the start of each month. Results: A certain intensity and duration of training effort during preparatory cycles (approximately 22–42% in the third intensity zone, 24–28% in the fourth intensity zone, and 3–4% in the fifth intensity zone) were necessary for athletes to achieve a high level of aerobic metabolism (64.00 and 69.40 mL·min−1·kg−1). Heart rate, work capacity at the second ventilatory threshold, the critical intensity limit, and maximum oxygen consumption were all shown to be vital indicators for predicting competition results. Conclusions: The identified indicators of physical development and functional capacity could aid in forming a team capable of reaching an elite level in the future.